Construction of a ferroptosis-related eight gene signature for predicting the prognosis and immune infiltration of thyroid cancer - Ren, Xiaoying; Du, Huijun; Cheng, Weilun; Wang, Yujing; Xu, Yuanxin; Yan, Shuang; Gao, Yunan (Frontiers in Endocrinology, 2022)
Background: Thyroid cancer is the most common malignant tumor of the endocrine system. Although most have a good prognosis, there are still some with recurrence and metastasis, resulting in a poor prognosis. Ferroptosis is a novel form of regulated cell death (RCD), and studies have confirmed that ferroptosis is associated with thyroid cancer. However, the prognostic value of ferroptosis-related genes in thyroid cancer and their impact on the thyroid cancer tumor microenvironment (TME) remain unclear. Methods: In this study, 497 thyroid cancer RNA expression data were downloaded from the TCGA cohort and a prognostic risk model for 8 ferroptosis-related genes was constructed using Lasso-Cox regression. The prognostic value of the risk model and the correlation of prognostic features with immune scores and tumor immune cell infiltration were systematically analyzed. Results: The prognostic risk model for eight FRGs (DPP4, TYRO3, TIMP1, CDKN2A, SNCA, NR4A1, IL6, and FABP4) were constructed and validated in training and testing cohorts. Kaplan-Meier curve and receiver operating characteristic (ROC) curve analysis confirmed that ferroptosis-related eight-gene signature has good predictive value for the prognosis of THCA patients.And multivariate regression analysis showed that the risk score of the prognostic model could be used as an independent prognostic factor for THCA patients.Functional enrichment analysis showed that DEGs in high-risk and low-risk groups were involved in immune-related biological processes ; immune cell infiltration showed statistical differences between the two risk groups. Conclusion: A new ferroptosis-related gene model can be used to predict the prognosis of thyroid cancer, and the new ferroptosis-related gene may be used for targeted therapy of thyroid cancer in the future.